ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE BERDASARKAN ASEAN CORPORATE GOVERNANCE SCORECARD PADA PT BPD BALI: ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE BERDASARKAN ASEAN CORPORATE GOVERNANCE SCORECARD PADA PT BPD BALI - Novia Sari; Putu Ngurah Suyatna Yasa; A.A. Gede Krisna Murti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2024)
This research aims to be able to evaluate the extent to which the implementation of various principles in the form of Good Corporate Governance at PT BPD Bali uses the ASEAN Corporate Governance Scorecard assessment framework which is an evaluation tool. This research focuses on three aspects of assessment, namely, first in the form of the role of stakeholders, second in the form of disclosure, and third in the form of transparency and the responsibility of two parties, namely the board of directors and also the board of commissioners. The research method used is a qualitative approach in the form of document content analysis guided by the ACGS assessment framework, using the steps of the Miles and Huberman analysis model. This research uses secondary data in the form of documents